A Game of Hare & Hounds An Operational-level Command Study of the Guilford Courthouse Campaign, 18 January-15 March 1781 - Allen Skinner, Harold Jr (Marine Corps University Press (MCUP), 2021)
How did a narrow tactical victory for the British at Guilford Courthouse, North Carolina, during the American Revolutionary War lead to the failure of the British Southern Campaign? This volume offers an indispensable point of departure for a staff ride to the battlefield at Guilford Courthouse, providing a systematic analysis of this key battle in the American Revolution. Author Harold Allen Skinner Jr.'s narrative establishes necessary context to illuminate the decisions that shaped the overall contest in the South between American and British armies. Skinner's deft presentation of the events leading up to and during the pivotal battle of Guilford Courthouse reveals insights at the three levels of war and provides a balanced treatment of issues, such as command at the strategic and operational levels and organization of armies, weapons, and tactics. His approach gets straight to the central purpose and greatest value of a staff ride: the critical process of analyzing how and why events played out as they did.